Metastatic Clear-Cell Renal Carcinoma: An Exceptional Cause of Ileocolonic Intussusception in Adults - Francisco E. Alvarez-Bautista; Alejandro Hoyos-Torres; Catherine Sarre-Lazcano; Juan J. Andrade-Rojas; Noel Salgado-Nesme (Journal of Coloproctology, 2023)
Introduction Intussusceptions in adults are rare, representing 1% to 5% of intestinal obstructions in this age group. This condition can be caused by benign and malignant lesions acting as lead points, the latter being the most frequent. Furthermore, the diagnosis is challenging due to the non-specific symptoms with variable duration. Case Presentation A 43-year-old man, with a history of localized clear-cell renal carcinoma (ccRCC) treated 9 years earlier with a right radical nephrectomy, presented with bowel obstruction symptoms. An abdominal computed tomography scan showed an ileocolonic intussusception. Hence, the patient required a right hemicolectomy with ileotransverse anastomosis. The histopathological analysis showed a metastatic ccRC to the terminal ileum causing the intussusception. Discussion Adult intussusceptions are rare. However, they should be considered in the differential diagnosis of patients with abdominal pain and symptoms of bowel obstruction. Metastases of renal cancer to the small bowel are uncommon and even more so in the form of intussusception. Definitive treatment must be tailored to the patient's condition and underlying cause.